种染料敏化太阳能电池NiS/CoS对电极的制备方法 (2018)
本发明公开了种染料敏化太阳能电池NiS/CoS对电极制备方法，具体是将含有过硫酸钾、硫酸镍和氨水的混合溶液倒入放有FTO导电基底的玻璃器皿中，静置，洗涤干燥，在FTO表面原位生长得到前驱体；再放入硝酸钴溶液中浸泡后取出并干燥；将用硝酸钴溶液浸泡过的FTO和硫源分别放入真空管式炉中，氩气保护升温至350℃~550℃，保温2小时，冷却后得到NiS/CoS对电极。本公开发明的NiS/CoS对电极制备工艺简单，形成纳米片与纳米颗粒的异质结，增加了电极的催化活性位点，并且垂直生长的纳米片结构有利于电解质的扩散，降低了扩散电阻，使其具有更高的电催化活性，从而提高了光电转化效率。 The invention discloses a preparation method for a NiS2/CoS2 counter electrode of a dye-sensitized solar cell. The preparation method comprises the steps of pouring a mixed solution containing potassium persulfate, nickel sulfate and ammonia water into glass ware loaded with an FTO conductive substrate, allowing the mixed solution to stand, performing washing and drying, and performing in-situ growth on an FTO surface to obtain a precursor; placing the precursor in cobalt nitrate solution for immersion, and taking out and drying the product; and respectively placing the FTO and a sulfur source which are immersed by the cobalt nitrate solution in a vacuum tubular furnace, rising a temperature to 350-550 DEG C under argon protect